2015
DOI: 10.1159/000441555
|View full text |Cite
|
Sign up to set email alerts
|

Personalised and Precision Medicine in Cancer Clinical Trials: Panacea for Progress or Pandora's Box?

Abstract: Cancer clinical trials have been one of the key foundations for significant advances in oncology. However, there is a clear recognition within the academic, care delivery and pharmaceutical/biotech communities that our current model of clinical trial discovery and development is no longer fit for purpose. Delivering transformative cancer care should increasingly be our mantra, rather than maintaining the status quo of, at best, the often miniscule incremental benefits that are observed with many current clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…A positive score in challenges [8][9][10] indicates that the authors identified the corresponding challenge and reported on the challenge in the publication. Negative scores indicate that the corresponding challenge is not addressed or identified and reported by the authors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A positive score in challenges [8][9][10] indicates that the authors identified the corresponding challenge and reported on the challenge in the publication. Negative scores indicate that the corresponding challenge is not addressed or identified and reported by the authors.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the use of randomized controlled trials (RCTs) for collecting evidence, and to inform health economic evaluations, is increasingly being questioned in a PM context [5][6][7][8][9]. RCTs are designed to draw conclusions on a population-level, while PM focusses on patient-level outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al proposed an ODE-based computational framework to implement virtual phase i trials in cancer, using an experimentally calibrated mathematical model of melanoma combination therapy, which can readily capture observed heterogeneous clinical outcomes and be used to optimize clinical trial design [120]. Lawler et al suggested potential solutions in precision medicine for clinical trial design that balanced the cost and value, to deliver cost-effective cancer care [121]. The benefits of Lawler's approach can be transferred directly to the patients [121].…”
Section: Current Three Hot Directions In Systems Biologymentioning
confidence: 99%
“…Lawler et al suggested potential solutions in precision medicine for clinical trial design that balanced the cost and value, to deliver cost-effective cancer care [121]. The benefits of Lawler's approach can be transferred directly to the patients [121]. …”
Section: Current Three Hot Directions In Systems Biologymentioning
confidence: 99%
“…Lawler and Sullivan [2] highlight the need to address the cost-value dilemma in PCM, moving beyond a simplistic ‘what the market can bear' approach to a more nuanced value-based pricing philosophy. Employing this approach and embedding this philosophy into cancer care pathways can help reward innovation that has truly transformative potential (as opposed to the marginal ‘me too' mentality that is potentially reducing therapeutic effectiveness in cancer clinical trials) [3] and allow the benefits of a value-centred PCM strategy to accrue for both patients and societies.…”
mentioning
confidence: 99%